BERLATIH DIRI DENGAN POLA HIDUP SEHAT SEJAK DINI - Ferry Rhendra P.P. Sitorus; Avelinus Lefaan (LPPM Uncen, 2020)
This healthy lifestyle training activity is intended for students around the Perumahan Polda-Bhayangkara Buper Distrik Heram Kota Jayapura Propinsi Papua. Healthy lifestyle training activities are intended for students because they are easier to train a healthy lifestyle from an early age. By knowing healthy behavior from an early age, the trainees will be easier to do it from the beginning so that the formation of healthy behaviors is more easily achieved. The focus of this activity is focused on healthy lifestyle material through eating, drinking, hand washing and bathing. There were twenty school children around this housing complex who participated in this activity. This activity is carried out for three days. Material about health, especially the benefits of hand washing, healthy food, healthy drinks and the benefits of regular and clean baths. Also carried out in this activity is practice and guidance on how to wash your hands properly with cleansing soap. Healthy eating and drinking activities are also carried out along with a menu of bolu cakes, green beans, pudding and milk. At the end of the training there were tools for brushing teeth, toothpaste, notebooks and stationery for them. Through this healthy lifestyle training program the participants gained insight into doing a healthy lifestyle, practiced some healthy behaviors and got a tooth brushing tool. The hope is that by practicing some of these healthy behaviors during the training, these can be continued in daily life with the support of various parties, especially in their family.Keywords: Healthy lifestyle, training, students, Jayapura, Papua